Hepatic protective effect of grape seed proanthocyanidin extract against Gleevec-induced apoptosis, liver Injury and Ki67 alterations in rats - Nawal Mohammed Al-Rasheed; Thanaa Ahmed El-Masry; Ehab Tousson; Hanan Mohammad Hassan; Areej Al-Ghadeer (Universidade de São Paulo, 2018)
ABSTRACT Gleevec (imatinib) is an antineoplastic chemotherapeutic agent used in the treatment of many types of cancer. The current study was conducted to examine the possible modifying effects of grape seeds proanthocyandins extract (GSPE) against apoptosis, liver injury and Ki67 alterations induced by Gleevec in male rats. 40 male albino rats were equally divided into four groups (First and second groups were control and GSPE groups; third group was Gleevec group and fourth group was treated with Gleevec and GSPE). Gleevec induced elevations in P53 and depletion of Bcl2 levels in liver tissues were compared with the control group. Liver sections in rats treated with Gleevec exhibited marked cellular infiltrations, vacuolar degeneration hepatocytes, numerous apoptotic cells, and congestion in central and portal veins, as well as a significant increase in the proliferating of Ki67 after Gleevec injection as compared with control group. In contrast, treatment with Gleevec and GSPE showed a moderate to good degree of improvement in hepatocytes with a significant increase in Ki67, a decrease in P53 and an increase in Bcl2 levels in liver tissues compared to treatment with Gleevec. Therefore, Gleevec induces apoptosis, injury and Ki67 changes in rat liver, whereas GSPE modulates these alternations.